ANALYSIS OF THE EFFECT OF VOLTAGE AND CURRENT X-RAY TUBE ON COMPUTED TOMOGRAPHY DOSE INDEX VALUE IN BODY AND HEAD PHANTOM - Nermina
In this final project, the effect of detector position, tube voltage, and tube current on the dose value have been investigated. This study aims to analyze the comparison of dose values on the CTDI phantom of the body and head with variations in tube voltage and current. Tube voltage values for tube voltage variations are 80 kV, 100 kV, and 120 kV. The tube current values for tube current variations are 50 mA, 100 mA, and 200 mA. The measurements were carried out with a Toshiba Alexion 16 MSCT, phantom CTDI from Gammex, and a pencil ionization chamber detector. From the measurements obtained, dose values for each detector position. Furthermore, data processing was carried out, and the ????????????????100 and ???????????????????????????? values were obtained. From this study, the average ratio of ????????????????100 values at the edges to the center for body and head phantoms was 1.97–2.56 and 1.12–1.18, respectively. The ????????????????100 values for tube voltage variations in the body and head phantoms were 5.75–54 mGy and 21.75–96.175 mGy, respectively. Meanwhile, the ????????????????100 values for tube current variations in the body and head phantoms were 5.25–54 mGy and 14.975–96.175 mGy, respectively. The percentage difference between the measured ???????????????????????????? value and the ???????????????????????????? console for tube voltage variations is 4.45%–16.25%. The percentage difference between the measured ???????????????????????????? value and the ???????????????????????????? console for tube current variations is 4.34%–9.65%. The ???????????????????????????? values for tube voltage and current variations are good because the percentage error is still within the tolerance limits recommended by BAPETEN (± 20%). From this study, the greater the tube voltage and current use, the greater the ????????????????100 and ???????????????????????????? values in both the body and head phantoms.